The dual process of prejudice: racism, nationalism, and sexism in the 2020 U.S. presidential election - Rusowicz, Aleksandra; Pratto, Felicia; Shook, Natalie (Frontiers in Social Psychology, 2024)
IntroductionModern racism, nationalism, and sexism have been proposed as major influences on contemporary U.S. politics. However, most work has not examined these interrelated factors together. Thus, it is unclear to what extent each form of prejudice uniquely contributes to political behavior. Furthermore, the potential motivations underlying the link between prejudice and politics have not been well elucidated. We sought to (1) determine the extent to which racism, sexism, and nationalism were uniquely associated with political outcomes in the 2020 U.S. presidential election and (2) use the dual-process motivational model to examine whether social dominance orientation (SDO) and right-wing authoritarianism (RWA) were potential motivations underlying the link between prejudice and political attitudes and behavior.MethodsA national sample of U.S. adults (N = 531) completed online questionnaires before and after the 2020 U.S. election. Structural equation modeling was used to test mediational models in which SDO and RWA prospectively predicted presidential candidate evaluations and vote choice indirectly through racism, sexism, and nationalism.ResultsWhen examined in conjunction, modern racism (not sexism or nationalism) was consistently associated with evaluations of both candidates and vote choice. Furthermore, SDO and RWA both exerted indirect effects on candidate evaluations and vote choice through modern racism.DiscussionThese results are aligned with previous findings indicating that racism plays a unique role in U.S. politics and may be motivated by status threat experienced by some majority group members.